Developing Android-Based Mobile Learning On Cell Structure And Functions Lesson Subject Topic To Optimize Grade XI Students’ Cognitive Comprehension - Muhammad Saefi; Betty Lukiati; Endang Suarsini (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstracts: The objective of this study is to develop an android-based mobile learning media for Cell Structure and Function lesson subject in compliance with ADDIE development mode. The developed mobile learning takes in general explanation, learning objective, animal and plant cells material explanation complemented with activities and cell exploration clip, evaluation questions, dictionary, and technical guidance. In addition, the reviews of media expert, material expert, and academicians have shown that the developed media is valid. Also, the response of students has proven that the practicality rate of the developed media is 84.65%-100% and the classical pass of Abstrl cognitive tests upon learning by way of the developed media is equal to 84.61%.Key Words: learning media, mobile learning, android system, cellAbstrak: Tujuan penelitian adalah mengembangkan media mobile learning berbasis android pada pembelajaran Struktur dan Fungsi Sel yang mengacu pada model pengembangan ADDIE. Mobile learning yang dikembangkan terdiri dari penjelasan umum, tujuan pembelajaran, pemaparan materi sel hewan dan tumbuhan yang dilengkapi aktivitas dan video jelajah sel, soal evaluasi, kamus, dan petunjuk penggunaan. Penilaian ahli media, ahli materi, dan praktisi pendidikan menunjukkan bahwa media yang dikembangkan valid. Tanggapan siswa menunjukkan bahwa tingkat kepraktisan media hasil pengem-bangan sebesar 84,65%-100% dan ketuntasan klasikal tes kognitif setelah pembelajaran menggunakan media yang dikembangkan sebesar 84,61%. Kata kunci: media pembelajaran, mobile learning, sistem android, sel